Prediction of the Academic Buoyancy and Academic Performance of Health Students at Semnan University of Medical Sciences Based on Their Perception of the Learning Environment - Ayat Rahmani; Taleb Askaripoor; Hamed Aghaei; Mohammad ebrahim Ghafari; Mehdi Mohammadian Mastanabad; Mohammad Ali Jalilvand; Hasan Irvani; Elahe kazemi; Amir Abedin Darkoush (Mazandaran University of Medical Sciences, 2020)
Introduction and purpose: Students' perceptions of the learning environment play a vital role in the process of education, buoyancy, and academic performance. This study aimed to investigate the capability of explaining the academic buoyancy and academic performance of health students of Semnan University of Medical Sciences, Semnan, Iran, based on their perception of learning environment. Methods: The statistical population of this descriptive-correlational study consisted of all health students who were studying at Semnan University of Medical Sciences, Semnan, Iran, in the academic year 2018-19. A total number of 138 students were selected through systematic random sampling. The data were collected using a Dundee Ready Educational Environment Measure (DREEM), academic buoyancy questionnaires, and grade point average. Moreover, simple and multiple regressions were used for data analysis.  Results: The results showed that 16.1% (R=0.408, R2=0.167, Adjusted R2=0.161, F=27.212, P<0.01) of the variance of academic buoyancy can be explained by the overall score of students' perception of the learning environment. Furthermore, according to the regression coefficients, the subscale of students' perception of educational climate had a significant role in explaining academic buoyancy. According to the findings of the study, 13.3% (R=0.373, R2=0.139, Adjusted R2=0.133, F=21.971, P<0.01) of the variance in academic performance could be explained by the overall score of students' perception of the learning environment. In addition, the subscales of students' perceptions of learning and social conditions of education had a significant role in explaining academic performance. Conclusion: Given the positive role of perception of the learning environment in explaining academic buoyancy and academic performance based on the study findings, it is very important to conduct comprehensive assessments, identify strengths and weaknesses, and perform educational interventions to enhance students' perception of the learning environment.